2015
DOI: 10.1007/s13312-015-0586-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intravenous colistin in children

Abstract: Colistimethate sodium is effective against carbapenem-resistant Gram-negative bacteria, and is safe in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Other studies revealed that the efficacy of colistin was 68%-100%, and colistin was reported to be a safe and efficient treatment of MDR A baumannii infections in children. [1][2][3][4][5] In our study we obtained sterile blood and BAL cultures during colistin treatment, supporting previous reports.…”
Section: Safety and Efficacy Of Intravenous Colistin Use For The Treatment Of Nosocomial Multidrugresistant Acinetobacter Baumannii Infecsupporting
confidence: 90%
See 2 more Smart Citations
“…Other studies revealed that the efficacy of colistin was 68%-100%, and colistin was reported to be a safe and efficient treatment of MDR A baumannii infections in children. [1][2][3][4][5] In our study we obtained sterile blood and BAL cultures during colistin treatment, supporting previous reports.…”
Section: Safety and Efficacy Of Intravenous Colistin Use For The Treatment Of Nosocomial Multidrugresistant Acinetobacter Baumannii Infecsupporting
confidence: 90%
“…2 However, studies including colistin treatment for MDR A baumannii in the pediatric population are limited. [3][4][5] In our study, our aim was to evaluate the efficacy and safety of intravenous colistin use in patients diagnosed with central line-associated bloodstream infection (CLABSI) or ventilator-associated pneumonia (VAP) caused by MDR A baumannii between January 2013 and January 2015 in the Dr. Behçet Uz Children Research And Training Hospital, İzmir, Turkey.…”
Section: Safety and Efficacy Of Intravenous Colistin Use For The Treatment Of Nosocomial Multidrugresistant Acinetobacter Baumannii Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10 There are a number of studies evaluating colistin-related nephrotoxicity in the pediatric age group. 11,12 However, such studies focusing on premature children are quite few. 13 The aim of this study was to investigate the incidence of colistin-related side effects in premature neonates and to determine risk factors.…”
mentioning
confidence: 99%
“…Neonates 50 000 -75 000 IU/kg/day in three divided dosages 16,19 75 000 -120 000 IU/kg/day in three divided dosages have been used in this population 15 Infants and children 75 000 -150 000 IU/kg/day in three divided dosages. 16,17 Inhalation CMS < 40kg: 500 000 IU every 12 hours > 40kg: 1 000 000 IU (1MU) every 12 hours 16,20…”
Section: Dosage Based On Colistimethate Sodium (Cms)mentioning
confidence: 99%